Comparison of Interlukin-10, Tumor Necrosis Factor-α and Complement-3 Levels among Bangladeshi Pregnant Women with or without Hepatitis E Virus Infection - Sultana, Rabeya; Parvin, Niilufa; Deb, Paroma; Munshi, Saif Ullah; Tabassum, Shahina (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Several plasma proteins are proposed as biomarkers for acute HEV infected patients, but have not been validated among pregnant Bangladeshi women infected with HEV. Objective: In this present study, levels of interlukin-10 (IL-10), tumor necrosis factor α (TNF-α) and complement-3 (C3) were measured among HEV infected pregnant women and were compared with pregnant and HEV infected women. Methodology: This comparative cross-sectional study was conducted among the pregnant women who were admitted to the Department of Medicine, Department of Obstetrics & Gynecology, and Department of Hepatology of Dhaka Medical College Hospital (DMCH) and Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh for 1 year period. The study population included acute HEV infected pregnant women (HEV-P), healthy pregnant women (HPC) and HEV-infected non-pregnant women (HEV-NP) of the same age group. Interlukin-10 (IL-10), Tumor necrosis factor α (TNF-α) and complement 3(C3) levels were quantified by enzyme linked immunosorbent assay (ELISA) and turbidometry, respectively. Result: A total number of 81 women were recruited for this study of which 31 cases were acute HEV infected pregnant women (HEV-P); 25 cases were healthy pregnant women (HPC) and 25 cases were HEV infected non-pregnant women (HEV-NP) of the same age group. The mean levels with SD of the C3 level showed significant difference (P; 0.05) between groups of HEV-P (67.73±38.24 mg/dl), HEV-NP (147.9±22.28 mg/dl) and HPC (182.6±17.49 mg/dl). Though plasma TNF-α did not show any significant change (P; .05) in any of the groups, the IL-10 level was elevated significantly (p; 0.05) in HEV infected pregnant patients (0.187±0.3 ng/ml) then the non-pregnant HEV patients (0.027 + .08 ng/ml) and pregnant women group (0.012±0.04 ng/ml). Conclusion: In conclusion, increased levels of C3 and IL-10 observed in HEV infected pregnant women. Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):157-161